The Relationship between Menstrual Hygiene Knowledge and Bahavior with Leucorrhoea (Flour Albus) Incidence among Adolescent - Sabela Riska Pratiwi; Sri Indra Kurnia (Indonesian Journal of Global Health Research, 2025)
Adolescence represents a critical developmental stage characterized by substantial physiological transformations, including the commencement of menstruation, which heightens susceptibility to reproductive health problems such as abnormal leucorrhoea (flour albus). This research sought to investigate the association between knowledge and menstrual personal hygiene practices with the occurrence of leucorrhoea among female adolescents at SMP Muhammadiyah 5 Surakarta. Method: Utilizing a quantitative analytical method with a cross-sectional study design, the research recruited 109 participants through stratified random sampling. Data collection employed validated and reliable questionnaires, and subsequent analysis was conducted using univariate and bivariate statistical techniques, specifically the Chi-Square test. The results demonstrated a significant relationship between knowledge level (P = 0.002) and personal hygiene behavior (P = 0.001) with the incidence of leucorrhoea. Although most respondents exhibited good knowledge and hygiene practices, some still experienced abnormal leucorrhoea, suggesting the influence of other factors, such as environmental conditions and hygiene implementation.